Transformação de modelos orientados a objetos em modelos de banco de dados objeto-relacional - Pereira, Marco Antonio (Universidade Federal de São Carlos, 2007)
In general, software systems implemented based on Object Oriented (OO) concepts persist their information in Relational Database (RDB) and more recently in Object Relational Database (ORDB), which support the OO paradigm concepts. Therefore, it is common to use OO Models for software system requirements specification whose information are persisted in ORDB. Thus, the transformation of OO Models into Database Models has been an issue of several researches, particularly in the case of ORDB Models. Motivated in researching the transformation of OO models in ORDB Models and in Codes Structured Query Language (SQL), this work investigated an approach based on the idea of model driven development of Object Management Group (OMG), Model Driven Architecture (MDA), and offered it in a prototype form built as extension of the Multiple Views CASE (MVCASE) tool. As main result of this research we have the application of an approach that helps the Software Engineer in the development of OO Models and its transformation into ORDB Models and consequent generation of SQL Codes
Keywords: Engenharia de software; UML; MDA; Banco de dados objeto-relacional; Transformação de modelos; SQL (Linguagem de programação de computador); CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO